The Experiences of Selected Teachers in Dasmarinas City During the Initial Implementation of Online Distance Learning (ODL) in the Philippines - Barrera, Lannie; Gomez, Abigail C.; Padernos, Jessy Lou F.; Jr., Primo P. Villanueva; Espinosa, Mark Jayson G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The challenges brought about by the COVID- 19 pandemic was not only on the health, economic, and medical sector. It also brought about drastic changes to the education sector. With the "No Child Would Be Left Behind" philosophy, the Department of Education ensured that classes would push through without face-to-face communication. This policy led to various Online Distance Learning (ODL) designs per Division or locality. This qualitative study done through narrative inquiry aims to determine the different challenges experienced and recommendations proposed by the ODL teachers in the actual delivery of education at this time of pandemic and inputs for a better implementation of the school learning continuity plan. Responses from fifteen participants from the Division of Dasmarinas yielded experiences by which various themes were extracted from the participants. Written interviews were sent to many public elementary and high school teachers experiencing the Online Distance Learning provided and designed by the Department of Education, and fifteen responded. Results have shown that the system processes affect both teachers and students. Thus, further study must be done to perfect the Learning Continuity Plan design, specifically ODL. It may be an abrupt change brought by the pandemic, but a more intensive and careful plan must be done for problems are coming in the chain and bigger.